Morphological and phylogenetical description of Dennisiomyces fibrillosus sp. nov. (Agaricales, Tricholomataceae) from the Pyrenees and the first record of the genus in Europe - Corriol, Gilles; Jargeat, Patricia (Phytotaxa, 2019)
Dennisiomyces fibrillosus sp. nov. is described as a new species based on morpho-anatomical and molecular analyses and on two collections from the northern slopes of the mid-occidental Pyrenees (France). Despite a certain deviance, the best genus currently available for this species is the mainly tropical and subtropical genus Dennisiomyces, so far unknown in Europe. The recorded differences and the relationships with the closest genera are discussed.